The Effect of Price, Brand Image, and Product Quality on The Purchase Decision of Honda Motorcycles at Anugrah Kencana Motor Palembang - Jonathan, Vinsent; Cholid, Idham (Jurnal Multidisiplin Sahombu, 2025)
Consumer purchasing decisions are influenced by various factors, including price, brand image, and product quality. This study seeks to explore how these variables impact consumers in choosing Honda motorbikes at Anugrah Kencana Motor Palembang. Using a descriptive quantitative approach, data were collected from 264 respondents who were selected through purposive sampling, a type of non-probability sampling. The data were then analyzed using multiple regression with SPSS version 27. The findings reveal that brand image, product quality, and location play a significant and positive role in shaping consumer purchasing decisions, both individually and simultaneously. This highlights the importance of a strong brand perception and high product standards in attracting buyers. Interestingly, the price variable does not have a significant effect, suggesting that consumers may prioritize other factors over cost when making their decisions. These insights provide valuable input for businesses to refine their marketing strategies and enhance customer satisfaction.